CONTRASTING TWO KAZAKH PROVERBIAL CALLS TO ACTION: USING DISCOURSE ECOLOGIES TO UNDERSTAND PROVERB MEANING-MAKING - Aasland, Erik (Proverbium - Yearbook, 2018)
Though of the same genre, two comparable proverbs from a given culture can operate in two distinct communicative spheres. Using an approach called discourse ecology, I explore the intertextual dynamics, semantics, and usage of two Kazakh proverbial calls to action. I consider the meaning and cultural background for each proverb. Based on searches of social media and a Kazakh corpus of news articles, I argue that one proverb operates in mass-media whereas the other is limited to use in interpersonal conversation and online chat forums. I conclude with considerations of the contrasting roles that the two comparable proverbs play in terms of representative and frame-aligning discourse for contemporary Kazakhs.